Enhancing the tenth graders’ self-efficacy in learning Social Studies through technology-based pedagogies - Bandibas Jr., Porferio S.; Bedon, Berlie Ann F.; Cabaltera, Ma.Glesilda N.; Lloren, Jessa Betty; Pacate, Lovely Joy M.; Bansale, Jay C. (CV. Yudhistt Fateeh, 2024)
This research aimed to improve students' self-efficacy in Social Studies using technology-based pedagogies. The study utilized mixed methods sequential explanatory design which involves quantitative and qualitative data. Pre- and post-assessments were used to measure the development of students’ test scores and supported by pre- and post-self-efficacy surveys to identify the changes in students’ levels of self-efficacy. The Wilcoxon signed-rank test was used to determine the significant difference in pre- and post-self-efficacy survey scores. At the same time a paired sample t-test was used to analyze the pre- and post-assessment scores. On the other hand, the data obtained from the interview on the students’ experiences was analyzed thematically using Colaizzi's descriptive phenomenological data analysis technique. Results showed that students’ self-efficacy in learning Social Studies has improved with increased student engagement, active participation, and a more vibrant learning environment while implementing the interventions. Furthermore, the study recommends that teachers integrate different technological tools in their classes to enhance students' self-efficacy.